Efektivitas Biaya Strategi DOTS Program Tuberkulosis antara Puskesmas dan Rumah Sakit Swasta Kota Depok - Ulya, Fikrotul; Thabrany, Hasbullah (UI Scholars Hub, 2018)
Global TB notification rate at 2016 was 77% and 46.5% in Southeast Asia. Indonesia last 5 years still remain at 32-33% where Depok City reached 58%. In Depok City, private sector contributed 18.7% of the notified TB case in 2016 although only 40% of private hospitals were involved. The aims of this study is to determine cost-effectiveness of DOTS strategy implementation at private hospital and Public Health Centre (PHC). Comparative study carried out for six months with cohort retrospective between PHC, DOTS and Non DOTS hospitals using 36 samples per group. The calculation of the societal perspective with microcosting based on tariffs, market prices and budget value. Output is Success Rate, where at PHC 86.1%, DOTS hospital 77.78% and Non DOTS hospital 63.89%. The addition cost providers especially person in charge at PHC and DOTS hospital increase success rate. The cost of TB treatment in PHC 42% of private hospital. ACER (Average Cost Effectiveness Ratio) is obtained that the hospital which carry out the DOTS strategy is cost effective. To increase 1% success rate of TB treatment costs Rp 10,084,572 with intervention DOTS programs into a private hospital. An Independen t test stated that cost-effectiveness societal perspectives on TB treatment has a significant difference between PHC, DOTS hospital and Non DOTS hospital .